Influence of forced-air precooling time on the changes in quality attributes and consumer acceptance of Musa AAA Berangan - Kuan, Chee Hao; Ahmad, Siti Hajar; Radu, Son; Yap, E. S. P.; Zamri, Mohd Zakwan; Shukor, N. I. A.; Tajidin, Nor Elliza; Ketaren, Bunga Raya (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2015)
A good temperature management, such as precooling and cold storage, can delay deterioration of fresh produce. In this study, different forced-air precooling times were applied on Musa AAA Berangan to investigate the influence of forced-air precooling time on the changes of quality attributes and consumer acceptance. The banana was subjected to forced-air precooling treatment (5 ± 1°C) for 0, 14, 50, and 120 min and then stored in a cold room (13 ± 1°C) for 2 weeks. Then, all the fruits were transferred to a ripening room (25 ± 2°C) and initiated to ripen with ethylene gas. Quality attributes analyses and sensory evaluations were conducted when the fruits reached maturity index 5. Quality parameters, such as soluble solids concentration, titratable acidity, pulp firmness, and peel colour, showed no significant differences when fruits were precooled at different times. Blackening of peel as a result of chilling injury occurred in fruits treated with forced-air precooling for 50 and 120 min. This blackening significantly influenced consumer acceptance, although it did not affect the pulp colour and taste.